Survey relationship between clinical faculties\' manner or teaching behaviors and ‎nursing students\' anxiety from students\' view point at Guilan University of ‎Medical Sciences, ‎‏2007‏ - shahrbanoo latifi; shahrokh maghsoodi; minoomitra chehrzad; abtin heydarzadeh (Guilan University of Medical Sciences, 2007)
Introduction: Students' perceptions of how clinical faculty behave and relate to them (both ‎positively and negatively) were noted to influence their anxiety levels and consequently their ‎ability to learn and perform safely and effectively.‎ Objective: This study aims to determine the relationship between clinical faculties' manner of ‎teaching behaviors and nursing students' anxiety from students' viewpoint at Guilan ‎University of Medical Sciences in ‎‏2007‏‎.‎ Materials and methods: In this descriptive corelational study ‎‏171‏‎ second, third and fourth ‎year baccalaureate nursing students completed three questionnaires: an investigator designed ‎students demographic data questionnaire, the clinical teaching survey and a self-evaluation ‎questionnaire, designed to measure state anxiety.‎ Results: Findings of the Pearson's correlations indicated there were moderate negative ‎correlations between the personally(r=‎‏-0.63‏‎, p<‎‏0.0001‏‎) and professionally(r=‎‏-0.47‏‎, p<‎‏0.0001‏‎) ‎teaching behaviors of clinical faculty and students' state of anxiety. Covariate analysis ‎revealed that indirectly, students' age, marital status and unit of clinical training effected ‎statistically significant on anxiety. ‎ Conclusion: Finding indicated that clinical faculty should be intentionally aware of how their ‎teaching behaviors are perceived by students and influence student anxiety during clinical ‎experiences.‎